Volume 3: Heat Transfer; Electric Power; Industrial and Cogeneration 2000
DOI: 10.1115/2000-gt-0280
|View full text |Cite
|
Sign up to set email alerts
|

Flow Visualisation in a Rotating Cavity With Axial Throughflow

Abstract: Annular cavities are found inside rotor shafts of turbomachines with an axial or radial throughflow of cooling air. In order to increase efficiency and system reliability, flow and heat transfer phenomena in those cavities have to be investigated in order to minimize thermal load. For research purposes an experimental rig is set up. This paper focuses on flow visualisation using a laser light sheet technique in a heated rotating cavity which is axially flown through by cooling air. Flow phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 0 publications
4
30
0
Order By: Relevance
“…Most engine applications involve open rotating cavities with an axial throughflow. Idealised single rotating cavities with an axial throughflow of air have been experimentally studied by Farthing et al [18,19] and Bohn et al [20]. Engine representative geometries have been studied by Long and co-workers [21][22][23], Atkins and Kanjirakkad [24], and Puttock-Brown and co-workers [25,26].…”
Section: Open Rotating Cavity With Axial Throughflowmentioning
confidence: 99%
See 1 more Smart Citation
“…Most engine applications involve open rotating cavities with an axial throughflow. Idealised single rotating cavities with an axial throughflow of air have been experimentally studied by Farthing et al [18,19] and Bohn et al [20]. Engine representative geometries have been studied by Long and co-workers [21][22][23], Atkins and Kanjirakkad [24], and Puttock-Brown and co-workers [25,26].…”
Section: Open Rotating Cavity With Axial Throughflowmentioning
confidence: 99%
“…Engine representative geometries have been studied by Long and co-workers [21][22][23], Atkins and Kanjirakkad [24], and Puttock-Brown and co-workers [25,26]. throughflow [18,20]. Long et al [23] carried out velocity measurements, using laser Doppler anemometry, in a multiple rotating cavity rig for two different gap sizes between the shaft and the disc bores.…”
Section: Open Rotating Cavity With Axial Throughflowmentioning
confidence: 99%
“…This model has been subsequently used by many researchers to describe the prevailing flow structure in a heated rotating cavity. Farthing, et al, 1992a) Bohn et al (Bohn, et al, 2000) conducted flow visualisation within a rotating cavity and reported a similar flow structure as Farthing et al (Farthing, et al, 1992a). The role of buoyancy on heat transfer in rotating cavities was the focus of Alexiou (Alexiou, 2000) whose measurements revealed that the flow in rotating cavities can be dominated by free convection, forced convection or both (Alexiou, et al, 2000;Long, et al, 2003).…”
Section: Introductionmentioning
confidence: 89%
“…Bohn et al [9] performed measurements of the flow and heat transfer in a rotating cavity with axial throughflow. A centrifugal arm and two vortices appeared in their observations, which were similar with that of Farthing et al [10].…”
Section: A N U S C R I P Tmentioning
confidence: 99%